Sorption Characteristics of 137Cs and 90Sr into Rembang and Sumedang Soils - Budi Setiawan; Yusran Dani; Nurmaya Arofah (Universitas Gadjah Mada, 2016)
In order to understand the sorption behavior of 137Cs and 90Sr into soil sample from Rembang and Subang, it is important to estimate the effect of contact time, ionic strength and concentration of metal ion in the solution. For this reason, the interaction of 137Cs and 90Sr with soil sample has been examined. The study performed at trace concentration ( 10-8 M) of CsCl and SrCl2, and batch method was used. NaCl has been selected as a representative of the ionic strength with 0.1; 0.5 and 1.0 M concentrations. Concentration of 10-8 10-4 M CsCl and SrCl2 were used for study the effect of Cs and Sr concentrations in solution. Apparent distribution coefficient was used to predict the sorption behavior. The sorption equilibrium of 137Cs and 90Sr into soil was attained after 5 days contacted with Kd value around 3300-4200 mL/g, where Kd was defined as the ratio of number of radionuclide activity absorbed in solid phase per-unit mass to the number of radionuclide activity remains is solution per-unit volume. Presence of NaCl as background salt in the solution affected Kd values due to competition among metal ions into soil samples. Increase of Cs or Sr concentration in solution made Kd value decreased drastically. This information is expected could provide an important input for the planning and design of radioactive waste disposal system in Java Island in the future.